VD_FINDINFO HC / 2023 / 478 vom 19. Juli 2023 - VD Tribunal cantonal (2023)
PROTECTION DE L'UNION CONJUGALE, MODIFICATION DES CIRCONSTANCES, OBLIGATION D'ENTRETIEN | 176 al. 1 ch. 1 CC, 179 al. 1 CC, 285 CC